Exploring Car Rental Growth Opportunities in an Emerging Market – Azerbaijan Case - Aliyev, Akif (My University, 2015)
Denay Alliance Services LLC is a company based in Baku (nearly 3 million inhabitants), the capital of Azerbaijan. The company started its operation with three vehicles in 2010 and currently has a fleet of 25 cars. Denay is a "Business to Business" oriented company and since its creation has targeted mainly foreign commercial customers and some local enterprises. Despite the fact that Denay Alliance Services is a developing company, its fleet serves well-known oil and oilfield companies such as Cooper Cameron Petrolem Inc., Nalco Champion Azerbaijan, Enermech LTD, Expo Group Eurasia. After five years of operation, the company was able to improve its office facilities and moved to Luxen Plaza business center. This new location offered better access to potential new customers. In its operational period to date, the five office employees have gained good business service experience and have been able to follow a unique system of sales and financial operation. This paper contains sections that describe the processes of the company as an existing business and in particular it explains the company's product/services redesign, car market analysis, marketing, financial and operational plans. There has been a car rental market in Azerbaijan (operations mainly concentrated in Baku) for more than twenty years, but there has been very little information gathered on the industry over this time. Reviewing several web resources as well as international reports I have had the opportunity to get acquainted to such car rental business concepts as UBER, LYFT, Zipcar, Car sharing and their impact on the car rental industry. It is clear that internationally recognized car rental companies went through drastic development processes to proof their brands and develop recognition. UBER has launched a luxury car service for its target customers in Baku, however it is not a competitor to Denay, since Denay is mainly oriented to long-term contracts with enterprises rather than private hire. Companies like Avis, Hertz and Aznur have a directly competitive business concept, which is relevant to Denay's activity. This paper also shows how the information for this investigation was collected. The methodology of the consulting project was based on primary research (interviews) and the analysis of existing data, as well as information available on Internet resources. It is important to outline that there were six questions defined, which helped to define the directions for improvement and the research objectives. The table developed for 22 car rental companies (Appendix #2) helps to understand the core services of the main competitors and other rival companies. The limited access to the internal data of the companies (like, turnover, fleet number, customer list) has made the market share definition difficult, however information obtained from its main competitors, through interviews, meetings and other resources, helped to define the market share of the company within the target business line (providing service to corporations). The proposals and recommendations given regarding the operation, financial and marketing plan, should lead the company to achieve brand recognition and increase market share. This should be achieved by creating new strategies prompting active penetration into the market.
Business Consulting Project
Keywords: Business; Rental automobiles -- Azerbaijan; Rental automobiles -- Azerbaijan -- Economic conditions; Rental automobiles -- Azerbaijan -- Case study